6ER-031 Roles and impacts of the pharmacist from 1990 to the present: literature review and research perspective. (2nd March 2018) - Ferrand, E; Lebel, D; Bergeron, M; Bussières, JF
Abstract : Background: There are an increasing number of publications concerning the roles and impacts of pharmacists. Decision makers, clinicians and patients need evidence to support an appropriate allocation of funds to better use the expertise of pharmacists. Purpose: To provide a profile of the roles and impacts of the pharmacist in the literature. Material and methods: Review of literature. Articles in English and French related to the roles and the impacts of the pharmacist were selected, according a reproducible search strategy from 1990 to September 2017 in Pubmed and Pubmed Central. The following variables were extracted: author, country, study plan, pharmaceutical activities, patient care programmes, diseases, outcomes (e.g. mortality, morbidity, costs, adverse events, medication errors, compliance, satisfaction, other) and a quality score. Outcome results were categorised as positive, neutral or negative. Only descriptive statistics were performed. Results: On 20 September, 2017, a total of 2323 articles were included on 100 themes (e.g. 41 pharmaceutical activities, 30 diseases and 29 patient care programmes). Studies were conducted in the United States (46.6%), multiple countries (8.2%), Canada (7.8%), France (6.2%), the United Kingdom (5.3%), Australia (3.6%) and other countries (19.3%). Studies were either cross-sectional (47%), retrospective (33%), prospective (18%) or uncategorised (12%). Outcomes included morbidity (22%), medication errors (11.7%), satisfaction (7.3%), adherence (6%), costs (5.6%), adverse reactions (3.7%), mortality (1.3%) and others (42.4%). Included studies reported 6784 descriptive indicators and 5108 outcome indicators (60% were positive, 39% neutral and 1% negative). The quality score of articles (n=1, 697) were either excellent (8.8%), acceptable (34.2%) or with methodological limitations (57%). Conclusion: This review of the literature confirms the extensive presence of pharmacists in numerous patient care programmes, treating different diseases and performing a variety of pharmaceutical activities. Most outcomes related to pharmaceutical activities were positive. However, a significant proportion of published studies had methodological limitations. Pharmacists need to be more exposed to evidence about their roles and their impact, both in community and hospital settings. Furthermore, increasing funding for evaluative research must be supported by external stakeholders in different countries to better understand the impact of pharmacists' activities. No conflict of interest